Analisis Pengaruh Strategi Digital Marketing Dan Kualitas Konten Media Sosial Terhadap Keputusan Pembelian Produk Skincare Euphoria Store Di Maumere - Lamapaha, Fernanda Maria Immaculata; Samosir, Magdalena Silawati; Sanga, Konstantinus Pati (Jurnal Projemen UNIPA, 2026)
The rapid development of digital technology has encouraged businesses, including skincare brands, to utilize social media as an effective marketing platform. This study aims to analyze the influence of digital marketing strategies and social media content quality on consumer purchase decisions for skincare products. This research employs a quantitative associative approach. Data were collected through questionnaires distributed to 97 respondents, selected using the Slovin formula. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial (t-test) and simultaneous (F-test) hypothesis testing, as well as the coefficient of determination (R²), with the assistance of SPSS. The results show that digital marketing strategies have a positive and significant influence on consumer purchase decisions. Furthermore, the quality of social media content also has a positive and significant influence on purchase decisions. Simultaneously, both variables significantly affect consumer purchase decisions. These findings indicate that effective digital marketing strategies, along with informative, engaging, and credible social media content, can enhance consumer interest and positively influence their purchasing decisions regarding skincare products.